2014
DOI: 10.2147/ijwh.s73944
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy, safety, and patient acceptability of ibandronate in the treatment of postmenopausal osteoporosis

Abstract: Several second-generation bisphosphonates (BPs) are approved in osteoporosis treatment. Efficacy and safety depends on potency of farnesyl pyrophosphate synthase (FPPS) inhibition, hydroxyapatite affinity, compliance and adherence. The latter may be influenced by frequency and route of administration. A literature search using “ibandronate”, “postmenopausal osteoporosis”, “fracture”, and “bone mineral density” (BMD) revealed 168 publications. The Phase III BONE study, using low dose 2.5 mg daily oral ibandrona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…The MOVER study (Nakamura et al 2013) revealed that IBN was comparable to daily oral RIS in terms of reducing the incidence of vertebral fracture in Japanese patients with OP. Oral IBN at 2.5 mg daily decreased the risk of vertebral fracture by approximately 50% over a 3-year treatment period in the phase III BONE study (Inderjeeth et al 2014). Moreover, no atypical fracture or osteonecrosis of the jaw occurred in these patients, likely due to the lower affinity of IBN for hydroxyapatite than other BPs apart from RIS (Inderjeeth et al 2014).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The MOVER study (Nakamura et al 2013) revealed that IBN was comparable to daily oral RIS in terms of reducing the incidence of vertebral fracture in Japanese patients with OP. Oral IBN at 2.5 mg daily decreased the risk of vertebral fracture by approximately 50% over a 3-year treatment period in the phase III BONE study (Inderjeeth et al 2014). Moreover, no atypical fracture or osteonecrosis of the jaw occurred in these patients, likely due to the lower affinity of IBN for hydroxyapatite than other BPs apart from RIS (Inderjeeth et al 2014).…”
Section: Introductionmentioning
confidence: 88%
“…Oral IBN at 2.5 mg daily decreased the risk of vertebral fracture by approximately 50% over a 3-year treatment period in the phase III BONE study (Inderjeeth et al 2014). Moreover, no atypical fracture or osteonecrosis of the jaw occurred in these patients, likely due to the lower affinity of IBN for hydroxyapatite than other BPs apart from RIS (Inderjeeth et al 2014). Thus, IBN represents a good therapeutic option in terms of fewer adverse effects than other BPs.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, Rakel et al have reported that patients should not lie down for 60 min before the first food or drink which could reduced patient compliance [3]. Alternatively, ibandronate (IBN) can be infused intravenously to enhance its bioavailability to as high as 100% [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, no atypical fracture or osteonecrosis of the jaw was detected in this clinical trial. IBN has a lower affinity for hydroxyapatite than other BPs apart from RIS [4]. Therefore, it might be a better option for osteoporotic treatment from the viewpoint of fewer adverse effects.…”
Section: Introductionmentioning
confidence: 99%